Harnessing African Natural Gas : A New Opportunity for Africa's Energy Agenda? - Santley, David; Schlotterer, Robert; Eberhard, Anton (World Bank, Washington, DC, 2014)
Sub-Saharan Africa's persistent power shortages act as a severe constraint on its economic and human development. Over the last several years, a series of major offshore gas discoveries in Mozambique and Tanzania have rekindled interest in expanding the use of natural gas to address the continent's power shortages. Once thought of as a Nigeria-only story, gas-to power in Sub-Saharan Africa is now being considered in a continent-wide context, both as a supplement to Africa's abundant hydropower resources and as a replacement for more carbon intensive coal and liquid fuels. But the concentration of gas resources in just a few countries and the virtual absence of gas transportation infrastructure create economic challenges to the wider adoption of gas as a power generation fuel, particularly in smaller countries that cannot achieve economies of scale in gas production and transportation. As a result, the timeline between the discovery of gas and its commercialization is often measured in decades. This study examines the economic conditions facing policy makers, planners, and commercial actors with a stake in gas-to-power development in Sub-Saharan Africa. It looks at the upstream, midstream, and downstream segments of the gas value chain to identify where the economics align in favor of gas-to-power development and where they do not.